Problem Keadilan Gender dan Hak-Hak Asasi Perempuan dalam Islam - Samsuri Samsuri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
This article explores the gender and human rights issues in the Islamic community, There are problems originally coming from interpretation of Islamic teachings that be gender biased. According to Riffat Hassan, a feminist of Muslim. World, it is-called as